Quantitative measurement of a mixture of mesophases cubic MCM-48 and hexagonal MCM-41 by 13C CP/MAS NMR. - Nur, Hadi; Guan, Lau Chin; Endud, Salasiah; Hamdan, Halimaton (Elsevier Science B.V., 2004)

(untitled)
Quantitative measurement of a mixture of cubic MCM-48 and hexagonal MCM-41 mesophases by means of 13C CP/MAS NMR was discussed. The synthesis of pure cubic MCM-48, pure hexagonal MCM-41 and mixed hexagonal-cubic phases were carried out via mixed cationic-neutral templating route. The result show that in a mixture of hexagonal-cubic phase the presence of MCM-48 at a certain level could not be identified by XRD due to the very weak reflections. The result also show that the technique can be applied to a wide range of mesoporous structures.